Investment behaviour of Generation Z in the Czech and Slovak Republic - Hrnek, Bohuš; de Batz de Trenquelléon, Laure Sabine Marie; Čajka, Radek, 1983-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This thesis investigates the investment behaviour of Generation Z in the Czech and Slovak Republics. With the increasing interest in personal finance and investment, understanding this cohort's investment preferences and behaviour is crucial for financial institutions and policymakers. Using a quantitative research approach, data were collected through an online survey of 100 respondents aged between 18 and 28. The survey was focused on investment behaviour, investment preferences, risk aversion, financial literacy and factors influencing investment decisions. This study's contribution is twofold: it provides insights into the investment behaviour of Generation Z in the Czech and Slovak Republics and provides implications for financial institutions and policymakers.
Vedoucí práce: Laure Sabine Marie de Batz de Trenquelléon
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses